Frequency of Wound Breakdown In Patients Undergoing Elective Versus Emergency Cesarean Section - Nayyer Sultana, Uzma Zia, Abida Riaz, Shirin Gul, Seemab Aashiq (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the frequency of the wound breakdown after elective versus emergency cesarean section. Study design: Prospective, comparative, descriptive study Place & Duration: Department of Obstetrics & Gynecology, Central Park Teaching hospital, Lahore for six months i.e. 12-2-2019 to 16-8-2019 Methodology: 180 females were enrolled in the study from labour room after fulfilling the inclusion and exclusion criteria. Two groups were formed i.e. emergency cesarean delivery and elective cesarean delivery. The frequency of both types of cesarean deliveries was noted. The risk factors that could lead to impaired wound healing were noted. Then the females were followed-up in OPD for 10 days to evaluate for presence or absence of wound breakdown in both groups. Females with wound breakdown were managed as per hospital protocols. Results: The mean age of the patients was 29.77±6.16years. The mean gestational age of the patients was 38.94±0.81 weeks. The women with normal BMI were 64 (35.65%), 58 (32.2%) were overweight and 58 (32.2%) were obese. In this study 97(53.9%) women underwent emergency C-section and the remaining 83(46.1%) women underwent elective C-section. There were 19(10.6%) patients with wound breakdown and 161(89.4%) without wound breakdown. Frequency of wound breakdown was significant higher among women who underwent emergency C-section i.e. Emergency: 19.6% vs. Elective: 0%, p-value=0.000. Conclusion: Frequency of wound breakdown was significantly higher in women who underwent emergency cesarean section.